Selected pregnancy variables in women with placental abruption - Procházka, Martin; Ľubušký, Marek; Slavík, Luděk; Hrachovec, Petr; Zielina, Petr; Kudela, Milan; Lindqvist, Pelle G (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2006)
OBJECTIVE: The aim of this study was to investigate risk factors for placental abruption and to determine if anamnestic variables such as inherited thrombosis or recurrent fetal loss might be used as a predictor for placental abruption. METHODS: A retrospective case-control study at the University Hospital, Palacky University, Olomouc, Czech Republic. One hundred and eighty women with placental abruptio out of 20,175 deliveries (0.79 %) who were compared to 196 unselected pregnant women. A detailed anamnesis was taken. RESULTS: Compared to controls, women with placental abruptio had a 12-fold increased prevalence of prior recurrent fetal loss and a 6-fold increased prevalence of inherited thrombosis. CONCLUSIONS: We found that recurrent fetal loss, and inherited thrombosis may be significant risk factors for placental abruptio.
Keywords: rizikové faktory; dospělí; Risk Factors; Pregnancy Complications; lidé; Female; Pregnancy; těhotenství; Case-Control Studies; Abruptio Placentae; komplikace těhotenství; studie případů a kontrol; Adult; ženské pohlaví; předčasné odlučování placenty; Humans